Kung fu panda - Osborne, Mark; Stevenson, John, 1959-; Aibel, Jonathan; Berger, Glenn; Reiff, Ethan; Voris, Cyrus; Black, Jack, 1969-; Hoffman, Dustin, 1937-; Jolie, Angelina, 1975-; McShane, Ian, 1942-; Cheng, Long, 1954-; Rogen, Seth, 1982-; et al. (Hollywood, Calif. : Paramount Home Entertainment, 2008)
Po works in his family's noodle shop while dreaming the day away about becoming a Kung Fu master. His dreams soon become reality when he is unexpectedly chosen to join the world of Kung Fu and study along side his idols. Before they know it, the vengeful and treacherous snow leopard Tai Lung is headed their way. It is now up to Po to defend everyone from the oncoming threat.
DVD release of the 2008 motion picture.
Special features: commentary with filmmakers ; "Meet the cast" featurette ; "Pushing the boundaries" the tech of Kung Fu Panda featurette ; "Sound design" featurette ; "Kung fu fighting" music video by Cee-Lo ; "Team Earth : wild pandas" conservation featurette ; DreamWorks Animation video jukebox ; "Mr. Ping's noodle house" with Alton Brown ; how to use chopsticks ; Dragon Warrior Training Academy ; printables ; weblinks.
Director of photography, Yong Duk Jhun ; editor, Clare Knight ; music, John Powell, Hans Zimmer.
Voices: Jack Black, Dustin Hoffman, Angelina Jolie, Ian McShane, Jackie Chan, Seth Rogen, Lucy Liu, David Cross, Randall Duk Kim, James Hong, Dan Fogler, Michael Clarke Duncan.
MPAA rating: PG; for sequences of martial arts action.
DVD, region 1; Dolby Digital 5.1 surround (English, Spanish and French) and Dolby Digital 2.0 stereo. surround (English).
Keywords: Pandas -- Drama; Kung fu -- Training -- Drama; Revenge -- Drama; Martial arts -- Drama; Animated films; Comedy films; Adventure films; Video (DVD)